Predictive value of the Framingham steatosis index for cardiovascular risk: a nationwide population-based cohort study - Cho, Yun Kyung; Kim, Myungjin; Kim, Ye-Jee; Jung, Chang Hee; Lee, Woo Je; Park, Joong-Yeol (Frontiers in Cardiovascular Medicine, 2023)
Background: Nonalcoholic fatty liver disease (NAFLD) is common and is associated with cardiovascular (CV) disease and mortality. The Framingham steatosis index (FSI) was recently proposed as a diagnostic marker of NAFLD and was calculated from age, body mass index, triglyceride, aspartate aminotransferase, alanine aminotransferase, diabetes history, and hypertension status. We aimed to evaluate the predictive ability of FSI for CV risk using a large-scale population dataset from the Korean National Health Insurance Service-National Health Screening Cohort (NHIS-HEALS). Methods: Among 514,866 individuals in the NHIS-HEALS, we excluded those who died, had a history of admission due to a CV event, and heavy drinkers. The final study cohort comprised 283,427 participants. We employed both unadjusted and covariate-adjusted models in Cox proportional hazards regression analyses. to determine the association between FSI and major adverse cardiovascular events (MACEs), CV events, and CV mortality. Results: During a median follow-up of 5.9 years, we documented 9674, 8798, and 1602 cases of MACEs, CV events, and CV mortality, respectively. The incidence of MACEs was 1.28%, 2.99%, 3.94%, and 4.82% in the 1st to 4th quartiles of FSI, respectively. The adjusted hazard ratios (HRs) [95% confidence interval (CI)] for MACEs gradually and significantly increased with the FSI quartiles (1.302 [1.215–1.395] in Q2, 1.487 [1.390–1.590] in Q3, and 1.792 [1.680–1.911] in Q4), following an adjustment for conventional CV risk factors, including age, sex, smoking, drinking, physical activities, low-density lipoprotein cholesterol, estimated glomerular filtration rate and waist circumference. Participants in the higher quartiles of FSI exhibited a noteworthy increase in the occurrence of CV event. However, upon adjusting for relevant risk factors, the association between FSI and CV mortality did not reach statistical significance. Conclusion: Our study suggests that the FSI, which is a surrogate marker of NAFLD, has a prognostic value for detecting individuals at a higher risk of CV events.